Marketing Strategy of Ayodya Resort Bali Hotel Through E-Commerce (Website) in Optimizing Room Occupancy Level - Ni Kadek Sudiasih Ari Artini Putri (Business Management, 2025)
This study aims to identify effective website-based e-commerce marketing strategies to increase room occupancy at Hotel Ayodya Resort Bali using a descriptive qualitative method and SWOT analysis. Data were collected through interviews, observation, documentation, and literature review, and analyzed using IFAS, EFAS, the IE Matrix, and the SWOT Matrix. IFAS results highlight key strengths, such as the hotel's strategic location and strong brand reputation (score 0.60), while weaknesses include low digital adaptability among staff (score 0.10), with a total IFAS score of 2.95. EFAS analysis shows opportunities in digitalization trends (score 0.60) and threats from intense five-star hotel competition (score 0.30), totaling 2.70. The IE Matrix places the hotel in the "grow and build" quadrant, suggesting a stability strategy. The SWOT analysis generates SO, WO, ST, and WT strategies, focusing on website optimization, staff digital skill development, strengthening local identity, and market diversification. Practically, the study demonstrates that website-based e-commerce improves promotional efficiency and room distribution, while theoretically confirming the effectiveness of SWOT and IE analysis in crafting sustainable digital marketing strategies in hospitality.